Biotic and abiotic drivers of macroinvertebrate assemblages in a South African river - Bellingan, Terence Andrew (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Aquatic insects are the most numerically abundant and diverse group of organisms found in lotic ecosystems in South Africa and the world over. They play vital roles in freshwater ecosystem functioning, processing nutrients and in turn forming integral links in stream food-webs. This thesis focussed on examining the macroinvertebrate fauna within three reaches of headwater streams of the Keiskamma River system: reaches that were considered to be fishless; reaches that were invaded by non-native salmonid species; and reaches that were dominated by native fish. I described the effects of predatory fish presence through detailed examination of macroinvertebrate assemblage composition; macroinvertebrate drift timing and density; and through niche utilisation determined from stable isotope data. Patterns in the macroinvertebrate assemblages of the headwaters of the Keiskamma River appear to be driven more strongly by flow rate and seasonal influences, but fish presence and biotope availability were also significant drivers. Niche shifts due to predator presence were not easy to detect and, while patterns of influence may have been evident, they were not found to be significant. However, I demonstrated that salmonids selectively feed on native fish species when the opportunity is presented, occupying significantly higher trophic levels when co-occurring with native fish than in invaded reaches where native fish are absent. Drift timing and density were demonstrated to be significantly different between reach for specific macroinvertebrate species from the Ephemeroptera and Plecoptera, under differing fish predation regimes, in agreement with what has been observed from studies in rivers elsewhere. In freshwater ecosystems of South Africa and worldwide, mitigation of negative effects of alien fishes through their removal using piscicides may also affect non-target organisms. To better understand the effects of just such a removal operation, employed for the first time in the history of freshwater conservation in South Africa, macroinvertebrate communities were assessed for non-target effects of rotenone. The fish eradication operations were demonstrated to have a short-term negative effect on the macroinvertebrate assemblage, through water quality index measurements and alteration of densities of macroinvertebrate taxa collected from stone surfaces. However, no long-term detrimental impact was observed as macroinvertebrate faunas returned to a comparable pre-treatment state within a year of each rotenone application.
Keywords: Aquatic insects -- South Africa -- Eastern Cape; Stream ecology -- South Africa -- Eastern Cape; Freshwater ecology -- South Africa -- Eastern Cape; Riparian areas -- Management; Ecosystem management -- South Africa -- Eastern Cape; Mayflies -- South Africa -- Eastern Cape; Stoneflies -- South Africa -- Eastern Cape; Keiskamma River